Comparison on polymerization of bulk-fill composite resins in different marginal thickness of tunnel restoration / SM Ab Ghani ... [et al.] - Ab Ghani, SM; Hassan, N S; Tamrin, A A; Lim, T W; Abu Hassan, M I; Ismail, M H (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Bulk-fill composite resins (BCR) was introduced with the advantage of 4-5mm depth of cured, thus an applicable material for a tunnel restoration. The study aimed to assess the polymerization of BCR with different marginal ridge thickness in tunnel restoration technique. Fifteen extracted teeth categorized into; G1=conventional proximal restoration (n:5), G2=tunnel 1.5mm marginal ridge thickness (n:5) and G3=tunnel 3.0mm marginal ridge thickness (n:5). Samples received the designated cavity preparation design and restored with BCR, embedded in resin and sectioned into halves. Each sample was tested with Vickers micro-hardness at the top (TP), middle (MP) and bottom part (BP) to get the micro-hardness value (VH). Data were statistically analyzed with 1-way ANOVA to compare means between groups and repeated measured ANOVA to compare means between the different areas. The mean micro-hardness (VH) value for top part (TP) G1=79.1, G2=77.3 and G3=74.9.; middle part (MP) G1=79.0, G2=73.3 and G3=74.9 and bottom part (BP) G1=71.1, G2=64.4 and G3=62.7. A decrease pattern of VH noted TP>MP>BP. No significant difference (p>0.05) VH for all groups for TP. For MP, significant difference (p<0.05) noted among the 3 groups and for BP, significant differences (p<0.05) between G1 to G2 and G3 only. In the same group, no statistical mean differences (p>0.05) were